Immunomonitoring of nuclear factor of activated T cells-regulated gene expression: the first clinical trial in liver allograft recipients - Zahn, Alexandra; Scheid, Nadja; Hinz, Ulf; Stremmel, Wolfgang; Schmidt, Jan; Ganten, Tom M.; Gotthardt, Daniel; Meuer, Stefan; Zeier, Martin; Giese, Thomas; Sommerer, Claudia (Liver transplantation, 2011)
Long-term calcineurin inhibitor (CNI) treatment can cause serious side effects in liver allograft recipients. An optimal risk-to-benefit ratio for CNI blood levels has not been established. Pharmacodynamic drug monitoring through the measurement of the CNI biological activity, that is, the expression of nuclear factor of activated T cells (NFAT)-regulated genes, seems to be a promising approach. The residual gene expression (RGE) of NFAT-regulated genes 2 and 1.5 hours after cyclosporine A (CsA) and tacrolimus (FK-506) intake was measured in 100 liver allograft recipients with 1 or more years of follow-up post-transplantation. The mean RGE in all patients was 62% ± 33%. A significant negative correlation between the CsA (P < 0.0001, r = −0.8026) and FK-506 peak levels (P < 0.0001, r = −0.6982) and the RGE of all NFAT-regulated genes was observed. Clinical reliability was proven too. In conclusion, the data presented in this pilot study reveal the applicability of the pharmacodynamic monitoring of CNI efficacy in liver allograft recipients. To confirm the advantage of individualized pharmacodynamic drug monitoring over pharmacokinetic drug monitoring with respect to clinical outcomes, controlled, prospective studies are needed. Liver Transpl, 2011. © 2011 AASLD.